THE STUDY OF MAKING GUAVA SLICED JAM (Psidium guajava Linn) - Ni Pande Made Lidya Paramesti; I Gusti Putu Sudita Puryana; Ni Putu Agustini (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Guava (Psidium guajava Linn) is tropical plant contains vitamins, mineral, fiber, and antioxidant. The 100 grams in red fruit guava vitamin c as many as 87 mg. Guava can be consumed by directly as well as processed into juice, jam, jelly, candied fruit dry, and new innovation slice jam. Slice jam is a modification jam product which was originally packaged in a jar into a compact and plastic slice. The principle of making jam is heating a mixture of crushed fruit, pectin or thickener, sugar, and acid. Pectin functions to thicken jam. The ideal amount of pectin for gel formation in jams ranges from 0,75 – 1,5%. The purpose of this study was to determine the right pectin concentration in order to obtain the appropriate characteristics in the manufacture of guava slice jam. The study design used was a Randomized Block Design (RBD) with four treatments and three replications so as to get 12 trials. With differences in concentrations of pectin 0,75%, 0,90%, 1%, and 1,5%. The parameters observed were organoleptic quality, vitamin C levels, and antioxidant capacity. Data were analyzed using analysis of variance, if there was an influence then continued the Smallest Significant Difference Test (LSD). The results showed that the most preferred product as a whole was slice jam with a pectin concentration of 1%. Based on the results of the objective quality analysis of guava jam produced, the levels of vitamin C were 31,7690 mg/100 grams, the antioxidant capacity was 283,34 mg/L GAEAC.Keywords: guava, slice jam, organoleptic, vitamin c, antioxidant